2012
DOI: 10.3109/00498254.2012.675094
|View full text |Cite
|
Sign up to set email alerts
|

3D-QSAR studies on UDP-glucuronosyltransferase 2B7 substrates using the pharmacophore and VolSurf approaches

Abstract: UDP-glucuronosyltransferase 2B7 (UGT2B7) is an important enzyme responsible for clearance of many drugs. Here, we report two 3D quantitative structure-activity relationship (QSAR) models for UGT2B7 using the pharmacophore and VolSurf approach, respectively. The dataset included 53 structurally diverse UGT2B7 substrates, 36 of which were used for the training set and 17 of which for the external test set. Pharmacophore-based 3D-QSAR model (or hypothesis) was developed using the Discovery Studio program. A user-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The pharmacophore model indicated that hydrogen-bonding acceptor played a significant role for the molecules glucuronidation by UGT1A8, consisting with the results of pharmacophore analysis for UGT1A3 and UGT2B7 [19,20]. Hydrogen-bond acceptor was regarded as a hydrophilic group.…”
Section: Discussionmentioning
confidence: 90%
“…The pharmacophore model indicated that hydrogen-bonding acceptor played a significant role for the molecules glucuronidation by UGT1A8, consisting with the results of pharmacophore analysis for UGT1A3 and UGT2B7 [19,20]. Hydrogen-bond acceptor was regarded as a hydrophilic group.…”
Section: Discussionmentioning
confidence: 90%
“…However, such models are uncommon for UGTs due to the lack of UGT crystal structures and challenges in protein expression. In the past, molecular modeling techniques, including two-dimensional (2D)- and three-dimensional (3D)- quantitative structure–activity relationship and pharmacophore modeling, were employed to understand molecular features of UGT1A1 and UGT2B7 substrates. , Here, for the first time, we are using a structure-based pharmacophore modeling approach to understand the molecular features determining UGT2B17–substrate interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A similar, pharmacophore-3D QSAR and VolSurf-3D QSAR approach was employed by Ako et al for the prediction of K m values for UGT2B7 substrates. 140 Modeling UGT2B7 substrate selectivity is inherently difficult, especially in the absence of crystallographic data, as it can accept both phenolic, alcoholic hydroxyl (e.g., estrogen and lipids), 141 carboxylic acid (e.g., ibuprofen), 142 and amino (e.g., carbamazepine) groups as SOG. For 53 substrates (36 in training and 17 in test set), experimental binding affinities were measured using recombinant enzyme systems.…”
Section: Udp-glucuronosyltransferase (Ugt)mentioning
confidence: 99%